Frequency of Profiling of Forensic Autopsies - Aisha Rasheed, Naseem Akhtar, Ishtiaque Ali Langah, Ijaz Aziz, Sono Mal, Azra Anwar (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To identify the profiling of medicolegal autopsies. Study design: Prospective observational study. Place and duration of study: Medicolegal Section, Liaquat University Hospital, Hyderabad from 1st January 2015 to 31st December 2019. Methodology: Nine hundred and eighty two autopsies of medicolegal nature were performed over a period of five years. The data was collected from forensic autopsy reports and was recorded with the consent of close relatives. Results: Majority of the subject was male (78.92%) and belonged to age group of ≥19 to <60 years. The number of subjects reported from urban locality (67.61%) was higher than rural areas (32.39%). The distribution of causes of deaths showed major contribution of road traffic accidents (45.32%) followed by fire arm injury (16.70%), asphyxia (15.31%), train accident (3.46%), and poisoning (1.83%). All of the causes of deaths were higher in males and within age group of adults. Most of the medicolegal nature causalities were reported from urban areas of the region. The number of forensic autopsies was highest in summer season (40.12%). Conclusion: The males outnumbered the females in medicolegal autopsies. The road traffic accidents had highest frequency of causing deaths in both genders and in all age groups irrespective of locality and seasons.